An analysis of citations to the fisheries research journal of the Philippines and Kalikasan, the Philippine journal of biology - Dizon, Leticia B.; Maclean, John L.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1991)
An investigation was made of citations to two Philippine biological journals, the Fisheries Research Journal of the Philippines (FRJP) and Kalikasan, the Philippine Journal of Biology using citation analysis, a scientometric/bibliometric tool. The aim was to find out how scientists use these journals.
The study yielded 313 citations to FRJP and 369 to Kalikasan. this was based on a sample of scientific journals, studies and reviews, conference papers, technical papers, master's theses, extension manuals, state of the art reviews and technical bulletins that covered the biological disciplines.
Results showed that SEAFDEC is the institution with the highest number of citations (106) to the journals. Primary literature, consisting of journals and studies and reviews is the document type with the highest number of citations (335). For total citations per year, FRJP and Kalikasan revealed an increase for all items combined. Most citations appeared in primary literature and conference papers. FRJP and Kalikasan articles were heavily cited from 0 to 6 years after publication; the average citation age is 4.4. thirteen authors received from 10 to 69 citations each. Eight articles had from 10 to 16 citations each.
Although the data do not show a very heavy use of the journals, they reveal that some impact was made on local science by these two journals. the study depicts the scientific activity of Philippine biological scientists. Recommendations for further studies are made.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Bibliographical citations; Fisheries--Research--Philippines--Bibliography.; Fisheries--Research--Philippines--Periodicals.